2020
DOI: 10.4028/www.scientific.net/kem.835.68
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution of NiTi Magnetron Sputtered Thin Film on Different Substrates

Abstract: Understanding the microstructure evolution of metal thin films on various substrates is essential for developing thin films that need specific requirements. The microstructure of thin films has been identified to be related to the mobility of the adatoms during growth. Recently, the theory of non-classical crystallisation of thin films has been introduced to explain the structure formation in chemical vapor deposition (CVD) and physical vapor deposition (PVD) processes. Much work has been conducted on CVD depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…As machining and forming the bulk NiTi alloy is a difficult and costly process, the application of NiTi alloy as raw material for surface coating is popularly considered. Abd EI-Fattah prepared NiTi thin films via magnetron sputtering on different substrates and found that crystalline structures were obtained on stainless-steel substrate [9]. Samal et al investigated thermal-plasma-sprayed NiTi coatings on AISI 304 substrate and found intermetallic phases like NiTi 2 , Ni 3 Ti and Ni 4 Ti 3 [10].…”
Section: Introductionmentioning
confidence: 99%
“…As machining and forming the bulk NiTi alloy is a difficult and costly process, the application of NiTi alloy as raw material for surface coating is popularly considered. Abd EI-Fattah prepared NiTi thin films via magnetron sputtering on different substrates and found that crystalline structures were obtained on stainless-steel substrate [9]. Samal et al investigated thermal-plasma-sprayed NiTi coatings on AISI 304 substrate and found intermetallic phases like NiTi 2 , Ni 3 Ti and Ni 4 Ti 3 [10].…”
Section: Introductionmentioning
confidence: 99%